KOMPOSISI PERBANDINGAN SUB SOIL DAN KOMPOS PENGGANTI TOP SOIL SEBAGAI MEDIA TANAM PADA PERTEMBUHAN BIBIT KARET SETELAH TRANSPLANTING - Wahyu Purnomo; Nurlaila; Hairu Suparto (Politeknik Pertanian Negeri Samarinda, 2019)
Growing media is very important for optimal plant growth and production, especially for planting media that have just been transplanted, so that suitable growing media is needed. The planting medium that is commonly used is top soil, because it contains many nutrients derived from the decomposition process of leaves that have fallen and root. However, the availability of top soil is limited to only + 30 cm from the soil surface. Whereas Sub soil is horizon B layer which is available in greater quantities but needs to improve the physical properties of sub soil so that it approaches the top soil properties, among others by adding compost. This purpose to determine the growth of rubber plants with composotion different planting media on rubber seed after transplanting. This research was in the Production Laboratory of the Study Program of Cultivation of Agriculture Plant in The State Agricultural Polytechnic at Samarinda for 4 (four) months. The treatment in this study was the comparison of the transplanting media of rubber seed, each repeated 5 (five) times, with 4 (four) treatment levels, are p0 = no treatment (control), p1 = comparison of planting media of rubber seed from top soil with sub soil of 1: 1, p2 = comparison of planting media of rubber seed from compost soil with sub soil of 1: 1, and p3 = comparison of planting media of rubber seedlings from compost soil with sub soil of 1: 2. The results of the study showed that the growth of rubber plant seedlings in the parameters of the number of leaves, stem deameter and plant height after transplanting using planting media from a mixture of sub soil with compost with a ratio of 1: 1 and 1: 2 is the same as the growth of rubber seedlings in the planting media of sub soil mixed with top soil.